Atherosclerotic Coronary Artery Disease in Patients With Cardiometabolic Syndrome - Miura, Shin-ichiro (Cardiol Res, 2019)
Major risk factors for cardiovascular disease (CVD) include aging, gender, smoking, family history and cardiometabolic syndrome. The relative residual risks for CVD after statin treatment for primary and secondary prevention have been reported by several large-scale randomized clinical trials. Statin treatment appears to prevent one-third of the onset and progression of CVD, but not the remaining two-thirds. There are three major problems regarding the residual risk of CVD: 1) Insufficient reduction of low-density lipoprotein cholesterol levels; 2) Low levels of high-density lipoprotein cholesterol and elevated triglyceride; and 3) Insufficient control of other risk factors (high blood pressure, obesity, metabolic syndrome, type 2 diabetes, etc.). Thus, a multifaceted preventive approach should be needed to prevent CVD after statin treatment.